2015
DOI: 10.1002/celc.201500045
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidation of Ammonia at Tuned (100)Pt Surfaces by using Epitaxial Thin Films

Abstract: PtxNi100−x thin films (72≤x≤100, 10–25 nm thick) were deposited on MgO (100) substrates by using pulsed laser deposition. As shown from X‐ray diffraction analysis, the formation of a Pt(Ni) solid solution was observed over the Ni range investigated. All PtNi‐based films showed epitaxial growth in the (100) direction at 350 °C, which is in contrast to pure Pt films, where a Ni seeding layer was required to obtain epitaxial deposits at this temperature. X‐ray photoelectron spectroscopy depth‐profile analyses sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…4,5 The polycrystalline surfaces of Pt, including (100), (111), and (533), have been employed as active substrates for ammonia decomposition to produce N 2 and H 2 . [6][7][8][9][10] However, the Pt catalysts for ammonia decomposition, including the use of doped Pt, 11 are to the best of our knowledge still not sufficiently effective at low temperatures (e.g., <350°C) and thus are not economically viable for large-scale applications. In view of this, there are ongoing efforts devoted to improving the Pt catalysis for ammonia decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The polycrystalline surfaces of Pt, including (100), (111), and (533), have been employed as active substrates for ammonia decomposition to produce N 2 and H 2 . [6][7][8][9][10] However, the Pt catalysts for ammonia decomposition, including the use of doped Pt, 11 are to the best of our knowledge still not sufficiently effective at low temperatures (e.g., <350°C) and thus are not economically viable for large-scale applications. In view of this, there are ongoing efforts devoted to improving the Pt catalysis for ammonia decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…MgO is chosen as a substrate because it is transparent, refractive, insulating, and does not react with Pt or Au, forming a clean atomically flat interface. Interface mixing reactions are a common problem with metal deposition on Si, which can form silicide precipitates at the interface and impact the epitaxial relationship 3 . MgO is also well lattice matched to many metals with face-centered-cubic symmetry and can grow biaxially textured on amorphous substrates, providing a path for large-area deposition of oriented films on amorphous substrates 4 .…”
mentioning
confidence: 99%
“…MgO is also well lattice matched to many metals with face-centered-cubic symmetry and can grow biaxially textured on amorphous substrates, providing a path for large-area deposition of oriented films on amorphous substrates 4 . The use of Fe or Ni layers to seed cube-on-cube epitaxy of Pt (100) on MgO (100) has been studied for catalysis applications 3 , however, these transition metals create deep level electronic defects in many semiconductors, and so are of less interest for photovoltaic film applications.…”
mentioning
confidence: 99%
“…Only for Ir nanoparticles did the CV curve exhibited an anodic current peak at 0.59 V (vs. RHE) ( Figure 3d). Such an oxidation current peak has been extensively reported on pure Ir and also Pt electrodes and is ascribed to the electro-oxidation of ammonia to N 2 [12,13,37]. Previous work performed CV measurements in the absence of ammonia and found that a such characteristic current peak did not appear [13,37,38].…”
Section: Resultsmentioning
confidence: 73%
“…On the other hand, ammonia is an environmental pollutant and a toxic gas. Therefore, the electro-oxidation of ammonia has important applications in direct fuel cells [8][9][10], hydrogen production [1,11,12], ammonia decomposition in wastewaters [8,13] and electrochemical sensors for detecting ammonia [14]. Since ammonia electro-oxidation is a sluggish reaction, electrocatalysts are required to catalyze the oxidation of ammonia to N 2 .…”
Section: Introductionmentioning
confidence: 99%